Stemness- and hypoxia-based prognostic stratification index reveals G6PD as a regulator of hypoxia-driven stemness in hepatocellular carcinoma - Gao, Mingwei; Liu, Yuechuan; Wu, Jianhui; Zhang, Peiru; Liu, Jin; Guo, Kun; Sun, Binwen; Ling, Sunbin; Wang, Liming (Frontiers in Immunology, 2025)
BackgroundThe positive feedback loop between cancer stemness and the hypoxic microenvironment is a critical driver of hepatocellular carcinoma (HCC) progression. Analyzing their interaction in HCC is crucial to characterize immune microenvironment features, uncover molecular heterogeneity patterns, and develop targeted interventions.MethodsThe TCGA-LIHC cohort (n=340) were stratified through consensus clustering of stemness- and hypoxia-related genes (SHRGs) identified by one-class logistic regression and weighted gene co-expression network analyses. Subsequently, a stemness- and hypoxia-related prognostic index (SHRPI) was constructed using random forest, and Cox regression analyses, with its prognostic significance assessed in two other independent cohorts: our NC-LT cohort comprising 180 liver transplant (LT) patients with HCC beyond Milan criteria, and the GSE104580 cohort containing 147 HCC patients treated with transcatheter arterial chemoembolization (TACE). A prognostic nomogram incorporating SHRPI was developed, and externally validated in the GSE14520 cohort (n=242). Systematic profiling of immune microenvironment features and immunotherapy responsiveness in SHRPI subgroups was performed, followed by pharmacogenomic screening and molecular docking to identify optimal therapies. After single-cell transcriptomic analysis, functional validation assays were conducted to confirm the role of G6PD, a key SHRPI component.ResultsSHRGs-based clustering revealed two clusters exhibiting distinct prognoses, functional annotations, genomic alterations, and immune microenvironment features. SHRPI served as an independent risk factor for both overall survival in HCC patients and recurrence-free survival in LT patients beyond Milan criteria. It demonstrated strong predictive power for TACE responsiveness. The SHRPI-integrated nomogram achieved robust performance in external validation. High SHRPI level was associated with a more immunosuppressive tumor microenvironment and poorer immunotherapy responsiveness. Pharmacogenomic and molecular docking analyses identified BI2536 as the most promising therapeutic agent for this high-SHRPI subgroup. Further experiments established that G6PD serves as a key therapeutic target for hypoxia-driven stemness maintenance in HCC by functioning as a stemness regulator that interacts with HIF-1α to form a positive feedback loop under hypoxia.ConclusionsThis study provides further insights into stemness-hypoxia interaction in HCC and delivers a clinically applicable predictive tool for prognosis. BI2536’s synergy potential and the therapeutic value of G6PD targeting in stemness regulation advance individualized therapeutic strategies for HCC.